PEMBERDAYAAN POTENSI LOKAL UBI JALAR SEBAGAI INOVASI DESA GUNUNG BUNDER II - Rifai, Muhamad; Efendi, Ramdan; Putri, Sulistiani Dwi; Saspira, Ratih; Fikri, Luthfy Rijalul; Lestari, Hana (Sahid Mengabdi: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2023)
This community service research aims to determine the local potential of the Gunung Bunder II village area which can be used as a village innovation. This Community Service research was conducted in Gunung Bunder II village with the subject of village community. This study uses qualitative descriptive method with data analysis in the form of phenomenological analysis to describe the condition of Gunung Bunder II village objectively. Data collection methods include observation and interviews. This study was conducted for less than three months starting from June 12 to September 9, 2023. From the results of the study, it was found that the Gunung Bunder II village area is rich in local plantation potential, one of which is sweet potato plantations. From the abundant local potential of sweet potatoes, it is used into an innovation called Terkasih (Sweet Potato Flour Silih Village).